An Assessment of the Academic Achievement of Students in Two Modes of Part-time Programme in Nigeria - Kola Adeyemi (Athabasca University Press, 2005)
This study analyses the academic achievement of students enrolled in part-times studies at on-campus and outreach centres at three dual-mode Nigerian universities, during the 1996/97 to 1998/ 99 academic years. Research subjects in this study were examination and record officers employed by on-campus and outreach institutions. A checklist was prepared to collect students’ grades; these checklists were then transcribed into grade points (GPAs) for data collection purposes. Simple percentage mean (x) and t-test statistic were used for data analysis. Interviews were also conducted with key stakeholders to add qualitative context to the quantitative data collected. This study shows that there was significant difference in the academic performance of students enrolled in the on-campus versus outreach-based, part-time programmes in selected disciplines. Also the average mean (x) performance of students enrolled in the on-campus programme was higher than those students enrolled in the outreach centres. Based on the findings of this study, it is recommended that the government provide adequate funding to increase access individuals seeking higher education in Nigeria. The establishment of functional Open University system is also recommended to provide students with distant learning opportunities and likewise increase access. Several quality improvements are likewise recommended: the use of modern information technology for instructional delivery, recruitment of skilled teachers, improved teaching/ learning facilities, and strict adherence to standardized student admission requirements as specified by the National Universities Commission (NUC). We wrap up with practical suggestions, such as providing orientation sessions for outreach students to learn practical skills such as how to access library materials.